2022
DOI: 10.1002/hcs2.21
|View full text |Cite
|
Sign up to set email alerts
|

The development and impact of adopting electronic health records in the United States: A brief overview and implications for nursing education

Abstract: At present, health-care systems in the United States face enormous challenges in providing quality care, characterized by safe, effective, efficient, patientcentered, timely, and equitable care while containing health-care costs [1,2]. To understand and address patients' increasingly complicated health-care needs, we need safe access to quality information that is characterized by integrity, reliability, and accuracy [3], and establish mutually beneficial relationships among a multidisciplinary team of profess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…In a study on the utilization of electronic health record systems, it was found that there was improved quality of care as patient related information was easily accessible amongst the healthcare team thereby reducing treatment duplication. 17 There was also a notable financial benefit as there was a reduction in medicine related expenses, billing errors, and improved capturing of charges for healthcare services by providers. 17 However, while these technological advancements offer efficiency and functionality improvements, caution is warranted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study on the utilization of electronic health record systems, it was found that there was improved quality of care as patient related information was easily accessible amongst the healthcare team thereby reducing treatment duplication. 17 There was also a notable financial benefit as there was a reduction in medicine related expenses, billing errors, and improved capturing of charges for healthcare services by providers. 17 However, while these technological advancements offer efficiency and functionality improvements, caution is warranted.…”
Section: Discussionmentioning
confidence: 99%
“… 17 There was also a notable financial benefit as there was a reduction in medicine related expenses, billing errors, and improved capturing of charges for healthcare services by providers. 17 However, while these technological advancements offer efficiency and functionality improvements, caution is warranted. There is the risk of misalignment of UHC principles as metropolitan areas may have greater digital access as opposed to rural areas, resulting in a disparity in service delivery operational processes.…”
Section: Discussionmentioning
confidence: 99%
“…This study highlights the misalignment of EMR processes with the existing workflow, which is a frequently discussed issue in EMR adoption. For instance, improper EMR usage may lead to user errors that exert an adverse impact on the patient's health [70,71]. These obstacles can affect the usability and compatibility of technology in existing processes, which can affect the adoption and acceptance of technology among physicians.…”
Section: Unified Theory Of Acceptance and Use Of Technology (Utaut)mentioning
confidence: 99%